Pengaruh Motivasi Diri, Penghargaan Finansial, Pertimbangan Pasar Kerja dan Kemampuan Akademik terhadap Minat Mahasiswa Akuntansi untuk Berkarir Sebagai Akuntan Publik - Yhoga Heru Pratama; Adolof Sairo Ngongo (Jurnal Literasi Akuntansi, 2025)
Purpose: The purpose of this study is to prove the influence of self-motivation, financial rewards, job market considerations and academic ability on accounting students' interest in pursuing a career as a public accountant. Method: This research uses quantitative methods and uses primary data. The sample used in this research was 120 respondents from the accounting faculty from eight universities, namely students from the Faculty of Accounting from Bachelorwiyata Tamansiswa University Yogyakarta, Negri Yogyakarta University, Ahmad Dahlan University, Mercubuana University Yogyakarta, Duta Wacana Christian University Yogyakarta, Amikom University Yogyakarta, Sanat Dharma University Yogyakarta, Alma Ata University Yogyakarta. This  research  method  uses  a  questionnaire,  then  processed  and analyzed with SPSS version 26. Finding: The results of this research in the form of self-motivation, job market considerations, and academic ability have a positive influence on accounting students' interest in pursuing a career as a public accountant. Meanwhile, financial awards have no effect on students' interest in pursuing a career as a public accountant Novelty: In previous studies, researchers focused more on financial rewards and job market considerations, while in the current research, researchers added students' self-motivation and academic abilities.